PENGARUH KEPUASAN KONSUMEN, CITRA MEREK, DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN PADA KONSUMEN TRANSPORTASI ONLINE MAXIM DI KARANGANYAR - Pujiani, Dewi; Praptiestrini, Praptiestrini; Aji, Ambyah Atas (Surakarta Management Journal, 2023)
This study aims to determine the effect of customer satisfaction, brand image, and trust toward consumer loyality to use Maxim online transportation services in Karanganyar. The data used in this study are primary and secondary data. The population of this research is a consumer of online transportation maxim in the essay. The population in this study was 100. This research uses descriptive research method with a sample size of 100 respondents. The results showed that based on multiple linear regression analysis showed that the variable customer satisfaction (X1), brand image (X2), trust (X3) had a positive influence on consumer loyalty. Based on the results of the t test, it shows that the variable customer satisfaction (X1), brand image (X2), trust (X3) have a significant effect on consumer loyalty (Y) to use Maxim online transportation services in Karanganyar. The variable customer satisfaction, brand image, and trust toward consumer loyalty simultaneously have a significant effect on consumer decision to use Maxim online transportation services in Karanganyar.